Knowledge, Attitude and Practices of Married Women of Reproductive Age Toward Uterine Prolapse - Abeela Azam, Nayyar Latif, Ulfat Tahira, Maliha Amjad, Kiran Amjad, Seemal Tajasar, Rida Naz (Pakistan Journal of Medical & Health Sciences, 2023)
Background: Uterine prolapse (UP) is a prevalent chronic problem in Pakistani women of reproductive age. A huge number of UP cases can be prevented with knowledge, attitudes, and practices. Objectives: The study aimed to create awareness among married women by KAP set. Place and Duration: This survey was conducted in District Dera Ismail Khan, during 2020-2021. Methodology: A total of 290 married women in the age group 20-40 years were participants in this survey. The participants were interviewed face-to-face using a semi-structured questionnaire. Results: The maximum (60.68%) women participated from rural areas than from urban areas (39.31%) who faced the UP. The majority (36.56%) of respondents responded that uterine prolapse is caused due to weakness in pelvic muscles followed by delivery by an unskilled person (27.58%), giving birth at an early age (20.68%), frequent childbearing (10.68%), and constipation (4.48%). Out of 290 participants, 47.58, 22.06 and 30.68% of the respondents had a positive, moderate, and negative attitude towards uterine prolapse, respectively. Conclusion: The respondents’ knowledge, attitudes, and practices toward UP had a statistically significant relationship with their marital status, age, educational status, and occupational status. Keywords: Uterine prolapse; Married Women; Attitude; Awareness; Knowledge; Pakistan.